Podejście umiarkowane w sporze o możliwość i użyteczność moralną kodyfikacji norm etycznych - Klimczuk, Andrzej (Annales. Etyka w Życiu Gospodarczym, 2014)
The popularisation of code elaboration addressed to various social groups is one of the features of the modern world. However, among researchers of this phenomenon a full consensus on the moral validity and usefulness of this activity does not exist. The article closely reviews the literature with regard to the reasons for the creation of a moderate position on the codification of ethical standards. The essay brings closer the main concepts of ethical codes and positions for their adoption and rejection. Attention is paid to ways of increasing the effectiveness of codes and the ethical decision-making procedure in a manner that undermines supporters and opponents of codification approaches.